'Buzz-and-pipeline' dynamics in Chinese science: the impact of interurban collaboration linkages on cities' innovation capacity. Issue 2 (1st February 2022) - Cao, Zhan; Derudder, Ben; Dai, Liang; Peng, Zhenwei
ABSTRACT: Drawing on the 'buzz-and-pipeline' framework, this paper examines the impact of intra- and interregional collaboration linkages on the innovation capacity of cities, as evidenced by the co-publication networks existing among 217 Chinese cities located in 20 city-regions. The results show that (1) intra- and interregional linkages have an inverted 'U'-shaped and positive relationship with innovation capacity, respectively; (2) the positive effects of intra- and interregional linkages on urban innovation can be enhanced when combined with triadic closure and structural holes, respectively; and (3) there exists a complementary relation between intra- and interregional linkages in facilitating cities' innovation capacity.